Capturing Human Trafficking Victimization Through Crime Reporting, United States, 2013-2016 - Farrell, Amy ([Verlag nicht ermittelbar], 2021)
Despite public attention to the problem of human trafficking, it has proven difficult to measure the problem. Improving the quality of information about human trafficking is critical to developing sound anti-trafficking policy. In support of this effort, in 2013 the Federal Bureau of Investigation incorporated human trafficking offenses in the Uniform Crime Reporting (UCR) program. Despite this achievement, there are many reasons to expect the UCR program to underreport human trafficking. Law enforcement agencies struggle to identify human trafficking and distinguishing it from other crimes. Additionally, human trafficking investigations may not be accurately classified in official data sources. Finally, human trafficking presents unique challenges to summary and incident-based crime reporting methods. For these reasons, it is important to understand how agencies identify and report human trafficking cases within the UCR program and what part of the population of human trafficking victims in a community are represented by UCR data. This study provides critical information to improve law enforcement identification and reporting of human trafficking. Coding criminal incidents investigated as human trafficking offenses in three US cities, supplemented by interviews with law and social service stakeholders in these locations, this study answers the following research questions: How are human trafficking cases identified and reported by the police? What sources of information about human trafficking exist outside of law enforcement data? What is the estimated disparity between actual instances of human trafficking and the number of human trafficking offenses reported to the UCR?